Wound breakdown reconstructed by reverse lateral arm flap after excision of heterotopic ossification of the elbow following severe burn injury: A case report - Akihiro Hirakawa; Yoshiyuki Ohno; Shingo Komura; Haruhiko Akiyama (Elsevier, 2017)
We report the case of a wound complication that was reconstructed by reverse lateral arm flap after excision of heterotopic ossification (HO) of the elbow in a patient with severe burns. Careful attention should be paid to wound complication and HO recurrence in patients undergoing surgical treatment for elbow HO following burn injury. Keywords: Burn, Heterotopic ossification, Elbow, Complication